Under his eye: a criação da cidade totalitária em The Handmaid's Tale - Farias Filho, Alexandre Carlos de Albuquerque (2022)
Fictional stories, whether from literature or audiovisual, play an important role in the construction of a society's thinking, as a catalyst for ideas and concepts through its imagination. But not only fiction has this influence on reality, but the opposite way is also constant, in which the time and place where a piece is created will directly influence its structuring, whether of ideologies, criticism or even the construction of narrative and spaces. This is what happens with the dystopias, fictional pieces that emerged in the early 20th century, which are characterized as the opposite of a utopia, bby highlighting the negative elements of a society, as in the case of the TV series, The Handmaid's Tale, which uses totalitarian spatial an ideological components to build its story and scenarios. That said, this research seeks to analyze the relation between fiction and reality in the dystopian work The Handmaid's Tale, with reference to the totalitarian cities of reality and other dystopian creations, seeking a better understanding of the architectural and urban structure of the series. For this, it is necessary to understand the tangible characteristics of the plans created for large cities while they were under the power of a totalitarian regime, as well as how The Handmaid's Tale fits into the characteristics of the dystopian fiction genre.